Tanggung Jawab Negara Terhadap Eksploitasi ABK Indonesia di Kapal China Long Xing 629 menurut Hukum Ketenagakerjaan dan dalam Perspekif Hukum Islam - Rizki, Dimas Ari; Irham, M. Iqbal (Nagari Law Review, 2023)
There are many cases of ship crew (ABK) who are treated inhumanely, exploited, and even not paid according to their work contracts, which is a violation of human rights in the form of serious degrading of human dignity. International and Indonesian laws have regulated the protection of the rights of foreign workers. However, implementing those regulations should be assessed to increase the protection of the rights of foreign workers, especially for foreign ship crue. The article examines the extent of the State's responsibility for exploiting ship crew and its protection based on Law Number 39 of 2004 and how to protect foreign ship crew from an Islamic law perspective. The study applies normative legal research, focusing on legal approaches, and content analysis applies library research, collecting information from various sources. This research examines the government's duties in protecting Indonesian migrant workers in China based on Law No. 39/2004. The research results show that if crew members are abused on a ship flying the flag of another country, then that country must exercise its jurisdiction, namely, prosecution and supervision, investigation, and examination. If the case of crew abuse involves Indonesia and China, then the two countries must work together to investigate the case. As a signing party to several International agreements such as CERD, UDHR, and ILO, the government of Indonesia is accountable for protecting Indonesian crews that work on foreign ships. From the perspective of Islamic law, crew members, as weak and vulnerable parties, have the right to receive protection. Therefore, the State, through the government, is obliged to protect the rights of crew members, which have been stipulated in law and agreed upon with the employer as a service provider.